FEMALE TOURISM WORKERS AND THE COVID-19 PANDEMIC - Santi Diwyarthi, Ni Made; Anom Kumbara, A.A. Ngurah; Wirawan, A.A. Bagus; Sirtha, I Nyoman (E-Journal of Cultural Studies; Vol 14 No 3 (2021): Volume 14, Number 3, August 2021DO - 10.24843/cs.2021.v14.i03.p02, 2021)
Women are vulnerable to the impact of the Covid-19 pandemic. This happened because the pandemic situation made companies generally cut the number of female workers for the first time for reasons of efficiency. This research reveals female tourism workers and the Covid-19 pandemic. The research method used is qualitative, with purposive sampling. The results of the study prove that the Covid-19 pandemic is destroying the business world globally, with the impact of 4500 female tourism workers in Nusa Dua (85%), with a loss of 9 trillion rupiah per month. This situation requires workers who are generally the first to be unpaid live. Keywords : women workers, tourism, pandemic, covid-19